作者:
JKLee (J.K.Lee)
2018-07-03 03:02:07※ 引述《AAQ8 ()》之銘言:
: https://i.imgur.com/roKGvQG.jpg
: https://i.imgur.com/X26fYT3.jpg
: 這一題還可以理解
: 不太懂的地方是在找(I-Mn)的反矩陣時
: 是從哪裡判斷要先設(I+aMn)的
: 麻煩各位了 謝謝
另一種解法:
(M_n)^2 = nk*M_n
=> (M_n)^2 - nk*M_n = O
令 f(x) = x^2 - nk*x
則 f(M_n) = O
又 f(x) = (1-x)[-x - (1-nk)] + (1-nk)
=> O = f(M_n) = (I - M_n)[-M_n - (1-nk)I] + (1-nk)I
=> (I - M_n) [-M_n - (1-nk)I] = -(1-nk)I
=> (I - M_n) [M_n + (1-nk)I]/(1-nk) = I
=> (I - M_n) [M_n/(1-nk) + I] = I
=> (I - M_n)^(-1) = M_n/(1-nk) + I